Case report: Late middle-aged features of FAM111A variant, Kenny–Caffey syndrome type 2-suggestive symptoms during a long follow-up - Ohmachi, Yuka; Urai, Shin; Bando, Hironori; Yokoi, Jun; Yamamoto, Masaaki; Kanie, Keitaro; Motomura, Yuma; Tsujimoto, Yasutaka; Sasaki, Yuriko; Oi, Yuka; Yamamoto, Naoki; Suzuki, Masaki; et al. (Frontiers in Endocrinology, 2023)
Kenny–Caffey syndrome type 2 (KCS2) is an extremely rare skeletal disorder involving hypoparathyroidism and short stature. It has an autosomal dominant pattern of inheritance and is caused by variants in the FAM111 trypsin-like peptidase A (FAM111A) gene. This disease is often difficult to diagnose due to a wide range of more common diseases manifesting hypoparathyroidism and short stature. Herein, we present the case of a 56-year-old female patient with idiopathic hypoparathyroidism and a short stature. The patient was treated for these conditions during childhood. Upon re-evaluating the etiology of KCS2, we suspected that the patient had the disorder because of clinical manifestations, such as cortical thickening and medullary stenosis of the bones, and lack of intellectual abnormalities. Genetic testing identified a heterozygous missense variant in the FAM111A gene (p.R569H). Interestingly, the patient also had bilateral sensorineural hearing loss and vestibular dysfunction, which have been rarely described in previous reports of pediatric cases. In KCS2, inner ear dysfunction due to Eustachian tube dysfunction may progress in middle age or later. However, this disease is now being reported in younger patients. Nevertheless, our case may be instructive of how such cases emerge chronically after middle age. Herein, we also provide a literature review of KCS2.